Development and evaluation of hand operated seed cleaner for small-holder farmers in East Hararghe, Oromia - Teshome Urge Jiru; Ibsa Aliyi Usmane (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2021)
Cleaning and grading are two final operations of high-quality grain production that are traditional method cleaning & separation of sorghum and maize. Farmers normally do by hand which have many problems. The farmers of East and West Hararghe Zones have a problem of high seed shortage to get improved seed at the right sowing time and du to absent of cleaning &separation machine to use local seed of good variety. To reduce the problem the hand operated seed cleaner machine horizontally vibrating air-screen type was designed, fabricated and its performance was evaluated with the main parts of centrifugal blower, eccentric unit & a set of reciprocating sieve with belt-pulley driven system. The machine separates product on the basis of the differences in their sizes and incorporate fan to remove light particles. The machine was constructed at the FARC workshop from locally available materials. The machine was tested for its cleaning efficiency & capacity with sorghum & maize at Damota arada and observed that, the maximum cleaning efficiency of the machine at moisture content of 18% & 19 were 80 % for sorghum and & 90 % for Maize, and its capacity was found 5.7 & 8.5 q/hr for sorghum & maize respectively, which is much better than that of traditional cleaning which have observed about 0.8 & 1.2 q/h for sorghum & maize respectively. During the test seeds of others crop & seeds of weeds were found below the range which is 300 & 200 unit/kg respectively. The newly developed low production cost machine has got a promising acceptance for its higher efficiency, higher capacity and lower lab our time energy requirement and accessibility to be used both for seed cleaning, grading and commercial use, and also due to its simplicity and locally manufactured, it showed a potential for wider adoption, as a result, experiments and/or demonstrations will be continued under the local Hararghe under farmers' conditions.